Analysis and Design of Coil Rolling Machines on Robot Solenoids using Macroergonomic MEAD and REBA Based on Arduino Microcontroller - Sukendar, Irwan; Arifin, Bustanul; Addin, Faathir Sukron (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2020)
The making of Indonesian soccer robot in the division of the Indonesian Football Robot Contest (KRSBI) especially in the process of coil rolling machines on a solenoid does not pay attention to ergonomic factors. The process of winding the wire on the solenoid is done using only the hands manually and in an un ergonomic body position, which is turning and bending. As a result, the convolution process lasts longer and in the wrong posture, causing fatigue and back pain. Macroergonomic Analysis and Design (MEAD) and Rapid Entire Body Assessment (REBA) approaches are used to analyze the posture of the wire. The solution is obtained by design and making an ergonomic and semi-automatic coil rolling machines to solenoid Robot based on the Arduino Microcontroller